"Education cannot cease": the experiences of parents of primary age children (age 4-11) in Northern Ireland during school closures due to COVID-19. Issue 4 (7th June 2023) - Bates, Jessica; Finlay, Jayne; O'Connor Bones, Una
ABSTRACT: This paper reports the research findings from an online survey of parents of primary-age pupils in Northern Ireland during the COVID-19 pandemic. The aims of the study were to explore how parents supported their child/ren's home learning; to ascertain the communication, guidance and resources between home and school; and to learn from the experiences of parents to enable more effective practices to be established should similar circumstances arise in the future. The survey yielded 2, 509 responses and highlighted the divergence of practices in relation to home-school communications across schools as well as the challenges experienced by parents, particularly those who had one or more children with special educational needs and/or those who had Free School Meal Entitlement. The study was guided by Epstein's Framework of the Six Types of Involvement, most specifically the spheres of parenting, learning from home, communication, collaborating with the community and decision-making . Within Epstein's framework, the challenges and tensions between family, school and work are explored. Recommendations are made that will be helpful to parents, schools, teacher-educators, policy-makers and researchers in informing the shape and delivery of education in Northern Ireland and internationally both during and following the challenge of the current COVID-19 pandemic and for similar situations that may arise in the future. The findings and conclusions are relevant not only to the Northern Ireland education context, but also make a valuable contribution to global dialogue on what this experience has revealed about inequities in education systems and how these should be addressed going forward.